The theory of endogenous monetary cicle in the explanation of the economic cicles. Perú: 2002-2014 - Rivas Santos, Pablo (2016)
This article systematically describes how monetary explanation of the business cycle explain show it influenced the monetary policy (in the short, medium and long term) economic cycles. The subject matter of suchan explanation is the ise of production and the subsequent global recession unavoidable.The essence of this explanation is that the Central Bank considered high interest rate market prompting the Central Bank to reduce it by an expansionary monetary policy (which maittain slow interest rate reference). This consideration induced him to take such a monetary policy that caused economic cycles.